Exploration of Service Quality's Impact on Customer Satisfaction - Hasrawati, Hasrawati; Asdar, Muh.; Ismail, Muhammad (SEIKO : Journal of Management & Business, 2023)
In the age of globalization, both state-owned and privately-owned public transportation companies face increasing competition. Because loyal consumers will continue to use services that they are secure with and satisfied with, as well as establish positive relationships with the company's employees, public transportation service providers must be able to acquire more loyal customers than new ones. New consumers use the service only once and have no desire to utilize the company's services again. The service quality dimensions for measuring client satisfaction are physical evidence, dependability, responsiveness, assurance, and empathy. These five aspects of service quality have a positive effect on customer satisfaction. The subject of this study is the Damri City Bus in Makassar. The research procedure involves the distribution of 65 questionnaires to Damri Bus passengers. After the results of the reliability and validity tests were obtained, they were analyzed using Multiple Linear Regression with the SPSS 17.0 for Windows program, which included classical assumption tests, multicollinearity tests, heteroscedasticity tests, normality tests, t-tests, f-tests, and R2 tests. Based on the analysis, it was determined that service quality (SERVQUAL) influences the level of customer satisfaction both individually and simultaneously, and that this relationship has been empirically demonstrated. Damri Bus Makassar City's consumer satisfaction is significantly influenced by physical evidence. Keywords: Service Quality; Reliability; Guarantee; Physical Evidence; Emphaty; Responsiveness; Customer Satisfaction.